Development of Spider Queen non-playable character in Miner Quest game using finite state machine. - Raja Ilham Maulidani Gumelar; Purba Daru Kusuma; Ashri Dinimaharawati (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
Digital technology has rapidly developed, opening new opportunities for educational games for young children. These games serve as alternative learning media due to children’s high interest in playing games. Miner Quest is a game designed using game maker language or GML and using gamemaker studio platform. It incorporates a finite state machine method for non-playable characters (NPC). The game focuses on completing missions, inspired by Super Mario Bros 2, where players collect mining materials such as coal and nickel. This study aims to assess the effectiveness of Miner Quest in educating young children implementing finite state machine systems for NPCs